EFFECT OF NUTRITIONAL COUNSELING BASED ON HEALTH BELIEF MODEL FOR OSTEOPOROSIS PREVENTION IN WOMEN: A QUASI-EXPERIMENTAL RESEARCH - Shobeiri, Fatemeh; Hesami, Elham; Khodakarami, Batul; Soltanian, Alireza (Journal of Postgraduate Medical Institute, 2016)
Objective: To study the effect of nutritional counseling according to health belief model (HBM) for osteoporosis preventive behaviors in women referring to health centers in Hamadan City, Iran. Methodology: This quasi-experimental research was performed among 80 women, which were allocated randomly into two groups of forty-members each of cases and controls. All participants filled the written informed consent. Four educational session classes were performed in the case group. Through three stages (before interposition, immediately after interposition, and two month after interposition) these groups were evaluated. Analysis of the data was performed by SPSS/18, using t test, chi square test, Fisher and repeated measurement test. P-value was considered significant if it was less than 0.05. Results: Important difference was not observed among the two groups in terms of age, menarche age, education, job and BMI. There was no considerable difference among the two groups in terms of the average scores of the different structures of this model before the intervention. Mean scores of the awareness and various structures of the model (perceived vulnerability, perceived severity, perceived benefits, perceived barriers and performance) were enhanced considerably in the case group over time (immediately after and two month) after interposition (P <0.05). Conclusion: Based on HBM, the training has positive impact on information, opinions and performances of females about osteoporosis and its prevention.